EFFICACY OF A HYDROLOGIC MODEL IN SIMULATING DISCHARGE FROM A LARGE MOUNTAINOUS CATCHMENT - Thorne R.; Woo M.-k. (My University, 2006)
Three sets of climatic input data from weather station observations and reanalysis products were compared for use in the simulation of streamflow for a large mountainous basin in subarctic Canada. These data sets are statistically different or show biases for most months. Yet, when they were used in conjunction with specific suites of parameters optimized for individual data sets, the hydrological model (SLURP) was able to simulate flows from these data sets which compare satisfactorily with measured discharge of the 275,000 km2 Liard catchment. The progressive downstream change in simulated discharge was scrutinized to reveal how and why, despite using inputs that are different, the model can simulate comparable basin outflows. It was found that through the effects of overestimating or under-adjusting the flow for various sub-basins, the model can simulate discharge that matches the measured Liard flow. This compensating mechanism enhances the flexibility of the model in producing acceptable outflow for a large catchment. © 2006 Elsevier B.V. All rights reserved.
Keywords: CLIMATE DATA; MODELING; MOUNTAIN BASIN; SLURP; STREAMFLOW SIMULATION